A New Approach to the Identification of Distillation Column Based on Hammerstein Model - K., Ramesh; Anwaruddin, Hisyam; Suriya Kumar, Sinnadurai (Hindawi Publishing Corporation, 2014)
Developing a suitable nonlinear model is the most challenging problem in the application of nonlinear model based controllers to distillation column. Hammerstein model consists of a nonlinear static element described by wavenet based nonlinear function, followed by a linear dynamic element described by the Output Error(OE) model was used in this study to represent the nonlinear dynamics of the distillation column. The model parameters were identified using iterative prediction-error minimization method. The model validation results proved that the Hammerstein model was capable of capturing the nonlinear dynamics of distillation column.